Uptake and translocation of phytochemical 2-benzoxazolinone (BOA) in radish seeds and seedlings - Chiapusio, Geneviève (Journal of experimental botany, 2004)
The molecular aspects of phytochemical interactions between plants, especially the process of phytochemical translocation by the target plant, remain challenging for those studying allelopathy. 2-Benzoxazolinone (BOA) is a natural chemical produced by rye (Secale cereale) and is known to have phytotoxic effects on weed seeds and seedlings. The translocation of BOA into target plants has been poorly investigated. Therefore, the total absorption of [ring U 14C] BOA was estimated by oxidizing whole seedlings of Raphanus sativus cv. for 8 days and quantifying the radioactivity. Non-radiolabelled BOA in seedlings was also estimated by HPLC. BOA applied at 10(-3) M was readily taken up by germinated radish at a rate of 1556 nmol g(-1) FW. At these same concentrations, BOA reduced radish germination by 50% and caused a delay in radicle elongation. Exogenous BOA was responsible for the observed germination inhibition. At a concentration of 10(-5) M, BOA was taken up by germinated seeds (31 nmol g(-1) FW), but this quantity did not affect radish germination. Labelled BOA was not mineralized in the culture medium during seedling growth as no 14CO2 was recovered. Both 10(-3) and 10(-5) M BOA were translocated into radish organs, mainly into roots and cotyledons. These organs were then identified as potential physiological target sites. Cotyledons remained the target sink (44% of the total radioactivity). The kinetics of BOA uptake at 10(-3) and 10(-5) M in radish seedlings was identical: BOA accumulation was proportional to its initial concentration. A comparison between radioactivity and HPLC quantification for 10(-3) M BOA indicated that BOA (along with some metabolites) could effectively be recovered in radish organs using chromatography